2021
DOI: 10.1126/science.abe6301
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic analysis reveals global-scale patterns of ocean nutrient limitation

Abstract: Nutrient supply regulates the activity of phytoplankton, but the global biogeography of nutrient limitation and co-limitation is poorly understood. Prochlorococcus adapt to local environments by gene gains and losses, and we used genomic changes as an indicator of adaptation to nutrient stress. We collected metagenomes from all major ocean regions as part of the Global Ocean Ship-based Hydrographic Investigations Program (Bio-GO-SHIP) and quantified shifts in genes involved in nitrogen, phosphorus, and iron as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
123
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(148 citation statements)
references
References 64 publications
10
123
0
Order By: Relevance
“…The continuing expansion of global-scale meta'omic surveys, such as BioGeoTraces Biller et al (2018) and Bio-GO-SHIP (Ustick et al, 2021), highlights the importance of developing scalable and automated methods to enable more complete analysis of these data. Metagenomic pipelines that specifically integrate steps for handling eukaryotic biology, such as the EukHeist pipeline, are vital as eukaryotes are important members of microbial communities, ranging from the ocean, to soil (Bailly et al, 2007) and human- (Lukeš et al, 2015) and animal-associated (Campo et al, 2019) environments.…”
Section: Discussionmentioning
confidence: 99%
“…The continuing expansion of global-scale meta'omic surveys, such as BioGeoTraces Biller et al (2018) and Bio-GO-SHIP (Ustick et al, 2021), highlights the importance of developing scalable and automated methods to enable more complete analysis of these data. Metagenomic pipelines that specifically integrate steps for handling eukaryotic biology, such as the EukHeist pipeline, are vital as eukaryotes are important members of microbial communities, ranging from the ocean, to soil (Bailly et al, 2007) and human- (Lukeš et al, 2015) and animal-associated (Campo et al, 2019) environments.…”
Section: Discussionmentioning
confidence: 99%
“…A set of mechanistic experiments within a single model demonstrated that minor parameter adjustments that altered the strength of iron limitation and its replacement by nitrogen limitation in the tropical Pacific led to large changes in both the magnitude and sign of changes to regional NPP (Tagliabue et al, 2020). It is highly likely that there is divergence in the representation of nutrient limitation regimes across CMIP5 and CMIP6 models, in part due to the paucity of observational constraints (Moore et al, 2013;Ustick et al, 2021). Indeed, it was notable that the emergent constraint that assessed NPP projections from CMIP5 using the co-variation of sea surface temperature and NPP anomalies (Kwiatkowski et al, 2017), was not able to strongly discriminate among different iron-nitrogen limitation scenarios (Tagliabue et al, 2020).…”
Section: Uncertainties In the Representation Of Biogeochemical Processesmentioning
confidence: 99%
“…Associated with the challenge of constraining the magnitude of present-day NPP is uncertain knowledge of the drivers of change and how inter-model differences in atmospheric and ocean physics cascade through ocean biogeochemical cycles to drive resource limitation of NPP. Knowledge is growing regarding the role of multiple concurrent factors regulating microbial activity (Saito et al, 2014;Browning et al, 2017;Caputi et al, 2019;Ustick et al, 2021). But how the emergence of these multiple drivers are affected by the climate responses of key physical components, like winds, in the Indo-Pacific region in particular, is a major knowledge gap.…”
Section: Future Efforts To Reduce Uncertainty In Npp Projectionsmentioning
confidence: 99%
“…Co has been shown to be the metallic cofactor for alkaline phosphatase in the hyperthermophile Thermotoga maritima (Wojciechowski et al, 2002), although Co substitution for Zn in marine cyanobacterial alkaline phosphatase is currently unconfirmed. The Pacific Ocean, in contrast, broadly shows less evidence for P limitation and more evidence for N and Fe stress in the oligotrophic gyres (Bonnet et al, 2008;Saito et al, 2014) and Fe and other trace metal stress in the upwelling regions of the subpolar gyre and equatorial Pacific (Boyd et al, 2004;Coale et al, 1996;Moore et al, 2013;Tsuda et al, 2005;Ustick et al, 2021). This difference in extent of P stress in the Pacific basin compared to the Atlantic was likely the reason for the more linear relationship between dCo and dPO4 throughout the upper Pacific Ocean.…”
Section: The Dco and Dpo4 Relationship Depicts Co Uptake Remineralization And Scavengingmentioning
confidence: 99%